FACTORS THAT INFLUENCE THE CORPORATE VALUE LISTED IN LQ 45 - Purwaningrum, Dwi; Shena Ananda Putri; Ayu Miranda Limbong (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2025)
Research Aims: This study examines the impact of liquidity and decision of investmenton corporation value in LQ-45 companies listed on the Indonesia Share Exchange (IDX) between 2019 and 2023. Design/methodology/approach: Purposive sampling used to select the sample, and 115 organizations were chosen as samples from a total population of 225 enterprises. The study method employs a quantitative approach utilizing secondary data from annual reports. A system of multiple linear regression was used to determine the influence of each independent variable on the dependent variable. Each variable was described using descriptive analysis and the classical assumption test was performed to evaluate the quality of the variables. Search Results: Liquidity and Invesment Decision has simultanoeus impact on corporate value, Liquidity doesn’t, affecting Corporate Value, meanwhile Investment decision positively impacting Corporate Value. Liquidity and decision of investmenthave an influential contribution to Corporation value of 25%. Theoretical Contribution and Originality: This study is expected to contribute to financial theory, particularly in understanding the dynamics of investment decisions. It will also provide practical recommendations to investors and corporate management on making more optimal decisions to boost Corporation value. Keywords include liquidity, investment decisions, corporate value, LQ-45, and the Indonesia Share Exchange